Analysis of changes in trends in the consumption rates of benzodiazepines and benzodiazepine-related drugs - Miguel Angel Fernández García; Antonio Olry de Labry Lima; Ingrid Ferrer Lopez; Clara Bermúdez-Tamayo (Taylor & Francis Group, 2018)
Background To analyse trends in the rates of consumption of benzodiazepine (BZD) anxiolytics, BZD hypnotics and non-BZD hypnotics and the association with contextual factors. Methods Descriptive time series study. Units of analysis were monthly dose per inhabitant per day (DID) and dose per medical card per day(DCD) of benzodiazepine(BZD anxiolytics(BZD-A), BZD hypnotics(BZD-H) and non-BZD hypnotics(Non-BZD-H) between January 2006-December 2015. We analysed 6 primary healthcare districts(PHD) and used defined daily doses (DDDs) to calculate the monthly DIDs(overall and by ATC group). Trends and monthly percentage change (MPC) were analysed through joinpoint regression. Results The annual DID increased by 26% overall, the trend was different across ATC groups. Consumption in BZD-A and BZD-H increased (27.1%,61.9%), consumption in Non-BZD-H decreased by 35%. There was high variability in DCD across the PHD, with an overall increase of 10.2%(5.7%-22.9%). By ATC, DCD increased by 10.4% in BZD-A(4.2%-22.2%) and by 44.2% in BZD-H(33.2%-76.5%). The overall DCD in the Non-BZD-H decreased by 42.1%(19.7%-50.8%). We found an initial upward trend in consumption of BZD-A until April/2008(monthly percentage change -MPC- +0.5%), followed by a slightly slower increase (+0.1%). No changes in trend were detected in BZD-H. In Non-BZD-H, we observed an upward trend until February/2013(+0.1%), followed by a sharp decrease until August/2013(−6.3%), and finally a slight decrease(−0.3%). Conclusions BZD consumption has increased in the last decade, with variability across areas. The changes in trends do not coincide with the financial crisis, introduction of prescriptions by active ingredient, electronic prescriptions or copayment. The only decrease in the Non-BZD-H may be linked to an intervention.